Multimodalidade e representações de cidades brasileiras em livros didáticos de português língua adicional - Vinícius Amado de Oliveira Ribeiro (2024)
The textbook occupies an important place in language teaching. He is often the one who dictates what is taught in the classroom and its content can vary according to the conception of language and approach to culture. However, certain topics are constantly found in materials with great differences between them. For example, books for high school are different from books for free courses. So are the different books for Elementary School I and books for the business environment. In all of them, the teaching of grammar points, for example, is a constant. It is also common for these books to be full of photos and some of them are of cities where the language taught is spoken. Alongside these images, there may be texts of the most varied genres that talk about them. Therefore, textbooks not only make students aware of the existence of cities, but teach them about them. Everything that is said and shown about cities contributes to the construction of representations of them. In this way, the research aims to verify the presence of cities in Portuguese Additional Language textbooks, whether in verbal or visual mode. The aim is to know which are more and less frequent and what is taught about them. Knowing this can clarify what is being taught about Brazil, which regions are the most and least present and consequently what is presented about the country to students. It is a bibliographical research, of a qualitative and quantitative nature and which was guided by the Theories of Social Representations and the Grammar of Visual Design. The corpus consisted of two books published in the last two decades. The results showed that São Paulo (SP) and Rio de Janeiro (RJ) are the two most cited in both and that Belo Horizonte (MG) was also very frequent in the most recent collection. In both books I realized that, contrary to what I assumed, few aspects of cities are thematized. Therefore, in none of the books did I find texts that spoke exhaustively about, for example, history, climatic aspects, population composition or other data. Both books showed a predominance of mentions of places in the Southeast region. However, the most recent publication book showed a greater number of places from other regions. Furthermore, there was a concern, in the oldest book, to raise critical awareness about the reality of Brazilian society .